Pengaruh Komik Makanan Sehat terhadap Pengetahuan Makanan Sehat pada Anak Usia Dini - Carissa Izza Shafa; Ferry Darmawan; Arif Hakim (Bandung Conference Series: Early Childhood Teacher Education, 2022)
Abstract. Healthy food is a major factor in the growth and development of early childhood, the nutrients in food affect the health and intelligence of children. Through the educational process provided in schools, children are able to form understanding and knowledge about healthy food. In Early Childhood Education learning activities cannot be separated from the use of learning media, one of which is the use of visual media. One of the visual communication media that is interesting for early childhood is comics. This comic media was developed into a book, namely Healthy Food Comics. The subjects in this study were 15 children aged 5-6 years. With a pre-experimental research design with an analytical design of "One-Group Pretest-Posttest Design". This study aims to determine the effect of using Healthy Food Comics media on the knowledge of children aged 5-6 years. The results showed that the average pre-test score was 6.67 and the post-test average increased to 11.6 with a very well developed score category, while the Wilcoxon difference test results obtained a sig. (2tailed) of 0.001 < from a probability value of 0.025 which shows significant results, that the alternative hypothesis (Ha) is accepted. In line with the results of recalling through interviews conducted on each child, they showed a good understanding of healthy food knowledge that had been conveyed through the Healthy Food Comics media. Abstrak. Makanan sehat menjadi faktor utama dalam tumbuh kembang anak usia dini, zat gizi dalam makanan berpengaruh pada kesehatan dan kecerdasan anak. Melalui proses pendidikan yang diberikan di sekolah mampu membentuk pemahaman dan pengetahuan anak untuk mengenal makanan sehat. Dalam Pendidikan Anak Usia Dini (PAUD) kegiatan pembelajaran tidak terlepas dari penggunaan media pembelajaran, salah satunya yaitu penggunaan media visual. Salah satu media komunikasi visual yang menarik bagi anak usia dini yaitu komik, Media komik ini dikembangkan menjadi sebuah buku yaitu Komik Makanan Sehat. Subjek dalam penelitian ini adalah anak usia 5-6 tahun berjumlah 15 orang. Dengan desain penelitian pra-eksperimental design dengan rancangan analisis “One-Group Pretest-Posttest Design”. Penelitian ini bertujuan untuk mengetahui pengaruh penggunan media Komik Makanan Sehat terhadap pengetahuan anak usia 5-6 tahun. Hasil penelitian menunjukkan nilai rata-rata pre-test sebesar 6,67 dan nilai rata-rata post-test meningkat menjadi sebesar 11,6 dengan kategori nilai berkembang sangat baik (BSB), sedangkan hasil uji beda Wilcoxon diperoleh nilai sig. (2tailed) sebesar 0,001 < dari nilai probabilitas 0,025 yang menunjukkan hasil signifikan, bahwa hipotesis alternative (Ha) diterima. Sejalan dengan hasil recalling melalui wawancara yang dilakukan pada setiap anak menunjukkan pemahaman yang baik mengenai pengetahuan makanan sehat yang telah disampaikan melalui media Komik Makanan Sehat.